A comparison of isolation and culture protocols for human amniotic mesenchymal stem cells. Issue 15 (3rd August 2022) - Naeem, Aisha; Gupta, Nikita; Naeem, Usra; Khan, Muhammad Jawad; Elrayess, Mohamed A.; Cui, Wanxing; Albanese, Chris
ABSTRACT: The successful translation of mesenchymal stem cells (MSCs) from bench to bedside is predicated upon their regenerative capabilities and immunomodulatory potential. Many challenges still exist in making MSCs a viable and cost-effective therapeutic option, due in part to the challenges of sourcing MSCs from adult tissues and inconsistencies in the characterization of MSCs. In many cases, adult MSC collection is an invasive procedure, and ethical concerns and age-related heterogeneity further complicate obtaining adult tissue derived MSCs at the scales needed for clinical applications. Alternative adult sources, such as post-partum associated tissues, offer distinct advantages to overcome these challenges. However, successful therapeutic applications rely on the efficient ex-vivo expansion of the stem cells while avoiding any culture-related phenotypic alterations, which requires optimized and standardized isolation, culture, and cell preservation methods. In this review, we have compared the isolation and culture methods for MSCs originating from the human amniotic membrane (hAMSCs) of the placenta to identify the elements that support the extended subculture potential of hAMSCs without compromising their immune-privileged, pluripotent regenerative potential. Abbreviations: AM: Human amniotic membrane; ASCs: Adipose tissue-derived stem cells; BM-MSCs: Bone marrow-mesenchymal stem cells; DMEM: Dulbecco's modified eagle medium; DT: Doubling time; EMEM: Eagle's modified essential medium; ESCM: Embryonic stem cell markers; ESCs: Embryonic stem cells; hAECs: Human amniotic epithelial cells; hAMSCs: Human amniotic mesenchymal stem cells; HLA: Human leukocyte antigen; HM: Hematopoietic markers; IM: Immunogenicity markers; MHC: Major histocompatibility complex; MSCs: Mesenchymal stem cells; MCSM: Mesenchymal cell surface markers; Nanog: NANOG homeobox; Oct: Octamer binding transcription factor 4; P: Passage; PM: Pluripotency markers; STRO-1: Stromal precursor antigen-1; SCP: Subculture potential; Sox-2: Sry-related HMG box gene 2; SSEA-4: Stage-specific embryonic antigen; TRA: Tumor rejection antigen